Optimized resonant pulsed power supplies with deadbeat: repetitive regulation - Ji, Chao; Clare, Jon C.; Zanchetta, Pericle (2016)
This paper presents a novel digital deadbeat + repetitive control (DBRC) strategy for output voltage regulation of pulsed power resonant converters used in high energy physics applications. The proposed converter contains three individual series resonant parallel loaded (SRPL) converter arms, which effectively mitigate the influence of resonant tank unbalances on the converter operation. The deadbeat controller is designed to produce fast dynamics of the voltage pulses during the system transient periods, while the repetitive controller is employed to counteract model uncertainties and component variations and hence to achieve a high performance and fine quality in the steady state